Suicidality in Patients with Substance Use Disorders: A Narrative Review - Vignesh Kuppusamy; Siddharth Sarkar; Yatan Pal Singh Balhara (Journal of Mental Health and Human Behaviour)
Substance use disorders (SUDs) have been associated with suicidality. Several types of SUDs have been associated with self-harm attempts, suicidal attempts, and completed suicides. There are various risk factors that have been associated with suicidality in individuals with SUDs. The literature on this aspect is wide, and hence, there is a scope for a narrative review that covers the various aspects of the relationship between suicidality and SUD, including consideration of preventive aspects. This narrative review presents the synthesis of the literature on the association of substance use and SUD with suicidality, the risk factors that predispose an individual with SUD to suicidal behavior, and what kind of measures can be taken to address suicidality among persons with SUD. Strong associations were reported between SUD and suicidality. A higher prevalence of self-harm in females with SUD was reported by certain studies. Comorbid mood disorders, psychotic disorders, personality traits, lack of formal education, unemployment, poor family support, high smoking rate, early age of drinking, and polydrug use were several risk factors for suicidality in SUD. Weaker evidence of an effective intervention to prevent suicide or reduce self-harm among people with SUDs was reported by several randomized control trials. Some studies recommended environmental interventions such as a reduction in the number of bars. Nevertheless, policy-level changes like increasing alcohol taxes have resulted in decreasing alcohol-related morbidity and mortality, violence, traffic crash fatalities, drunk driving, rates of sexually transmitted diseases and risky sexual behavior, other drug use, and crime but failed to establish a statistically significant reduction in suicidal rates associated with SUD.